The TPx protein of Taenia solium metacestode regulates Treg and Th17 cell differentiation via the TGF-β/Smad signaling pathway - Sun, Xiaoqing; Mu, Qianqian; Zhou, Biying (Frontiers in Immunology, 2026)
IntroductionThe immunopathogenesis of cysticercosis remains elusive. This study investigates the effects of Taenia solium metacestode-derived thioredoxin peroxidase (TPx) protein on regulatory T (Treg) cells and T helper 17 (Th17) cell differentiation, as well as its correlation with signaling pathways in human Jurkat T lymphocytes exposed to TPx for varying durations, to provide a scientific basis for further studying the immune pathogenesis and clinical treatment of cysticercosis.MethodsTPx protein from the excretory-secretory antigens of T. solium metacestode was used to stimulate Jurkat cells at various timepoints. Flow cytometry was employed to detect the expression of CD4+CD25+CD127- Treg cells and CD4+IL-17A+ Th17 cells. Transcriptomic analysis was performed to identify the signaling pathways related to the differentiation of Jurkat cells under the influence of the TPx protein at different time points. The expression levels of TGF-β1, TGF-βR2, Smad4, Foxp3, RORC(γt), and phosphorylated Smad3 proteins were measured in TPx-treated cells and control cells at different time points.ResultsA Treg/Th17 cell imbalance was detected in Jurkat cells following exposure to TPx, characterized by a Treg-mediated predominant immunosuppressive response. Gene Set Enrichment Analysis identified significant enrichment of the TGF-β signaling pathway and Th17 cell differentiation pathway in TPx-treated cells. TPx significantly upregulated TGF-β1, TGF-βR2, and p-Smad3 expression in cells (P < 0.05). Concurrently, the expression of Foxp3, a key transcriptional regulator of Treg cell differentiation, was markedly increased (P < 0.05). In contrast, the expression of RORC(γt), a transcription factor critical for Th17 cell differentiation, showed significant reduction after 72 h of TPx induction (P < 0.05).DiscussionThe TGF-β/Smad signaling pathway is a crucial molecular mechanism involved in the imbalance of Treg/Th17 cells induced by the TPx protein of T. solium metacestode.